2008
DOI: 10.2174/156800908785133150
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cell Growth by Estrogen Signaling and Potential Targets in Thyroid Cancer

Abstract: Thyroid cancer occurs three times more frequently in females than in males, and in females the incidence decreases after menopause. This gender difference suggests that the growth and progression of thyroid cancer may be influenced by female sex hormones, particularly estrogens. Experimental data have clearly demonstrated that estrogens can influence cancer cell growth. The action of estrogens on target sites is mediated through related but distinct estrogen receptors, designated estrogen receptor alpha (ERalp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
127
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(139 citation statements)
references
References 0 publications
5
127
0
7
Order By: Relevance
“…The expression pattern of ER isoforms has been demonstrated in neoplastic and non-cancerous human thyroid tissues; however, the results are not consistent (19,20). Experimental studies have revealed that estrogen affects PTC development by interacting with ER at the level of target thyroid cells, thereby promoting the proliferation of mutated follicular cells (23). In addition, several different thyroid cancer cell lines have been revealed Tumor size, n (%) to express ER (24)(25)(26), and the proliferation of these cells was stimulated by ERα agonists, and downregulated by ERβ agonists (23).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The expression pattern of ER isoforms has been demonstrated in neoplastic and non-cancerous human thyroid tissues; however, the results are not consistent (19,20). Experimental studies have revealed that estrogen affects PTC development by interacting with ER at the level of target thyroid cells, thereby promoting the proliferation of mutated follicular cells (23). In addition, several different thyroid cancer cell lines have been revealed Tumor size, n (%) to express ER (24)(25)(26), and the proliferation of these cells was stimulated by ERα agonists, and downregulated by ERβ agonists (23).…”
Section: Discussionmentioning
confidence: 97%
“…Experimental studies have revealed that estrogen affects PTC development by interacting with ER at the level of target thyroid cells, thereby promoting the proliferation of mutated follicular cells (23). In addition, several different thyroid cancer cell lines have been revealed Tumor size, n (%) to express ER (24)(25)(26), and the proliferation of these cells was stimulated by ERα agonists, and downregulated by ERβ agonists (23). Consistently, the present study revealed that the expression of ERα is increased in PTC tissues, compared with the expression in NTG tissues.…”
Section: Discussionmentioning
confidence: 99%
“…6), can be explained by the finding that cell growth is primarily regulated via ERa, whereas ERb is involved in the control of apoptosis and suppressive functions (Chen et al 2008). In taking this view, two recent reports that correlated ERa positivity and loss of ERb expression in differentiated thyroid carcinomas with a more aggressive phenotype and a poor outcome are of interest (Heikkila et al 2012, Magri et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have revealed inhibitory effects of the estrogen receptor beta on the development of thyroid cancer (15,16). A recent epidemiologic study has also demonstrated a better prognosis in younger female patients (!55 years), before menopause, and those aged O55 years had similar outcomes to those of male patients, suggesting a sex disparity in thyroid cancer outcomes (10).…”
Section: Discussionmentioning
confidence: 99%